Adaptasi Masyarakat terhadap Dampak Sosial dan Lingkungan Industrialisasi di Desa Dawuan Tengah Kecamatan Cikampek Kabupaten Karawang - Yani Sri Astuti; Adha Dwi Azzahra Hidayat; Yasfi Fauziah; Naisya Rahma Salsabila; Billy Mayza Fajar Assidiq; Muhammad Hafidh Maulana Rahman (Geosfera: Jurnal Penelitian Geografi, 2026)
Industrialization, as part of economic development, drives the transformation of a region from an agrarian to an industrial one, but also creates complex social and environmental problems. Changes in livelihoods, the emergence of social disparities, and the decline in environmental quality indicate that communities need to adapt to survive. This study aims to analyze the forms of community adaptation to the social and environmental impacts of industrialization in Dawuan Tengah Village, Cikampek District, Karawang Regency. The method used is descriptive qualitative with data collection techniques through in-depth interviews and field observations. Informants were determined purposively based on certain criteria and data were analyzed through stages of transcription, coding, categorization, and drawing conclusions. The results show that industrialization has a positive impact in the form of increased employment opportunities, income, and the development of local economic enterprises. However, industrialization also has negative impacts in the form of changes in social interaction patterns to become more individualistic, air pollution due to industrial activities and logistics vehicles, noise, congestion, and changes in land use. These conditions indicate pressure on the quality and sustainability of the community's residential environment. The community adapts through job diversification, lifestyle changes, and increased environmental awareness. Thus, industrialization has a multidimensional impact, so sustainable management is needed to create a balance between economic growth and the quality of life of the community.